Ukiran Motif Kerawang Gayo, Gambaran Seni Kriya Kayu yang Nyaris Hilang - Nenggih Susilowati (Berkala Arkeologi Sangkhakala, 2009)
AbstractAs the time flow, Gayo people hadn’t built the traditional houses yet. Around late 19 to begin 20 century, the old building known as archaeological remains that had to be conservated. The architectured or it’s carved indicated the culture development of the past. That building also had known as a monument which indicated that at that time there’s an artistic skill and the glory of its art.